2017
DOI: 10.1016/j.jth.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Understanding parents' school travel choices: A qualitative study using the Theoretical Domains Framework

Abstract: Traffic related air pollution is detrimental to health and creates a substantial attributable mortality burden. It is suggested that a shift from motorised transport to active forms of travel will therefore have significant health benefits. Currently 46% of school journeys for primary aged children are made by car and this figure has risen steadily. Understanding barriers to active school travel (AST) is an important first step in developing behavioural interventions to increase active travel. The purpose of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 52 publications
4
39
0
2
Order By: Relevance
“…Second, we did not use the TDF to inform the development of the interview topic guide. Doing so may have obtained greater detail about the role of each domain in influencing the target behaviour as is noted in other studies 31 32. Equally, the easy mapping of the naturally occurring themes to the TDF domains validates its usefulness in this research area.…”
Section: Discussionmentioning
confidence: 70%
“…Second, we did not use the TDF to inform the development of the interview topic guide. Doing so may have obtained greater detail about the role of each domain in influencing the target behaviour as is noted in other studies 31 32. Equally, the easy mapping of the naturally occurring themes to the TDF domains validates its usefulness in this research area.…”
Section: Discussionmentioning
confidence: 70%
“…Moreover, the study reported that half of the children walked or used a bicycle for school travel. A study conducted in Yorkshire, United Kingdom [9], reported that the distance, time constraints, and parent's safety concern were the main barriers to active transportation. A study conducted in Dunedin, New Zealand [31], reported that approximately 51 percent of adolescents were admitted in the nearest school, which showed a five times higher rate of walking and lower motorization rates compared to their counterparts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The parent's income, car ownership, and socioeconomic status are positively related to car use for school children, while these factors show a negative relationship with walking/bicycling. The distance and safety concerns have been found to be pivotal barriers for the parents towards active transportation [9].…”
Section: Introductionmentioning
confidence: 99%
“…Second, this review provides a comprehensive documentation of all aspects related to intervention design and methodology. The focus is centered on methodology for a few reasons; principally, because recent research has discussed the importance of intervention sustainability, 25 programming, 26 and collaboration 27 in relation to improving AST. Finally, this review generates a pragmatic discussion for practitioners.…”
Section: Current State Of Reviews and Justificationmentioning
confidence: 99%